Monty Python and the Holy Grail [videorecording (Blu-Ray)] - Gilliam, Terry; Gilliam, Terry; Jones, Terry, 1942-2020; Jones, Terry, 1942-2020; Chapman, Graham, 1941-1989; Chapman, Graham, 1941-1989; Cleese, John; Cleese, John; Idle, Eric; Idle, Eric; Palin, Michael; Palin, Michael; et al. (Sony Pictures Home Entertainment, 2015)
In this spoof of the legend of King Arthur, the king recruits the Knights of the Round Table. He is soon joined by Sir Bedevere the Wise, Sir Lancelot the Brave, Sir Galahad the Chaste and the Pure, Sir Robin the Not-Quite-So-Brave-As-Sir-Lancelot, and Sir Not-Appearing-In-This-Film. God sends them on a quest to find the Holy Grail. Along the way they encounter a plague-ridden community, the Knights who say Ni, a killer rabbit, and more.